A two-dimensional thin Co-MOF nanosheet as a nanozyme with high oxidase-like activity for GSH detection. (18th May 2022) - Han, Miaomiao; Ren, Mengzhen; Li, Zhaohui; Qu, Lingbo; Yu, Lanlan
Abstract : A two-dimensional thin Co-MOF (ZIF-67) nanosheet with high oxidase-like activity was applied for sensitive visual GSH detection. Abstract : Nanozymes with the advantages of excellent enzyme-mimicking activity, low cost and high stability have displayed great application potential in diverse fields as replacements for natural enzymes. In this study, a new nanozyme based on an ultrathin two-dimensional metal–organic framework nanomaterial D-ZIF-67 was prepared and characterized. D-ZIF-67 exhibited remarkable oxidase-like activity, which was attributed to the large specific surface area of the two-dimensional sheet structure, as well as its numerous exposed active sites compared with crystal MOFs. In the catalytic process of D-ZIF-67, the hydroxyl radical and superoxide anion played an essential role and facilitated the oxidation of the substrate 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by oxygen. The reducing agent glutathione (GSH) inhibited the catalytic activity of D-ZIF-67 besides reducing the oxidized oxTMB, based on which a simple, sensitive and accurate colorimetric method was developed to determine GSH, with the detection limit of 229.2 nM. This work mainly proposes a new two-dimensional metal–organic framework with high oxidase-like activity and provides a simple and practical platform for visual GSH detection by naked eyes.